CD36 Is a Marker of Human Adipocyte Progenitors with Pronounced Adipogenic and Triglyceride Accumulation Potential. (18th May 2017) - Gao, Hui; Volat, Fanny; Sandhow, Lakshmi; Galitzky, Jean; Nguyen, Thuy; Esteve, David; Åström, Gaby; Mejhert, Niklas; Ledoux, Severine; Thalamas, Claire; Arner, Peter; Guillemot, Jean-Claude; et al.
Abstract : White adipose tissue (WAT) expands in part through adipogenesis, a process involving fat cell generation and fatty acid (FA) storage into triglycerides (TGs). Several findings suggest that inter-individual and regional variations in adipogenesis are linked to metabolic complications. We aimed to identify cellular markers that define human adipocyte progenitors (APs) with pronounced adipogenic/TG storage ability. Using an unbiased single cell screen of passaged human adipose-derived stromal cells (hADSCs), we identified cell clones with similar proliferation rates but discordant capabilities to undergo adipogenic differentiation. Transcriptomic analyses prior to induction of differentiation showed that adipogenic clones displayed a significantly higher expression of CD36, encoding the scavenger receptor CD36. CD36+ hADSCs, in comparison with CD36-cells, displayed almost complete adipogenic differentiation while CD36 RNAi attenuated lipid accumulation. Similar findings were observed in primary CD45-/CD34+/CD31-APs isolated from human WAT where the subpopulation of MSCA1+/CD36+ cells displayed a significantly higher differentiation degree/TG storage capacity than MSCA1+/CD36-cells. Functional analyses in vitro and ex vivo confirmed that CD36 conferred APs an increased capacity to take up FAs thereby facilitating terminal differentiation. Among primary APs from subcutaneous femoral, abdominal and visceral human WAT, the fraction of CD36+ cells was significantly higher in depots associated with higher adipogenesis and reduced metabolic risk (i.e., femoral WAT). We conclude that CD36 marks APs with pronounced adipogenic potential, most probably by facilitating lipid uptake. This may be of value in developing human adipocyte cell clones and possibly in linking regional variations in adipogenesis to metabolic phenotype.